Ibn Malik's Approach in Presenting Syntactic and Morphological Judgements; A study in Alfiyah - Toukhi, Shahd Sabir; Rajhi, Hanan Ahmed (Journal of Arabic Language Sciences and Literature, 2023)
This study attempted to examine Ibn Malik's method for conveying grammatical and morphological rules: a study in Al-Alfiyya. It examined the odd grammatical and morphological issues presented by Ibn Malik in his Alfiyyah. They included twelve issues in several grammatical and morphological chapters. I utilised the works of Al-Alfiyyah commentators to discuss them. I also examined other books on Al-Alfiyyah in order to examine Ibn Malik's perspectives, options, and techniques with regard to these grammatical rules.The problem is based on the following questions: (i) What is the method used by Ibn Malik to present the uncommon grammatical and morphological rules and what are the controls that he followed in his arrangement of the rules? (ii) What is Ibn Malik's position on issues of disagreement regarding the grammatical and morphological arrangement of the uncommon rules and what is the extent of agreement and difference between the commentators on Ibn Malik’s methodology in presenting the uncommon rules in his Alfiyah? iii) What is the effect of the rhyming on the presentation of the uncommon rules by Ibn Malik in his Khulasah (Summary)? The study utilised a descriptive inductive methodology. It collected and categorised the data, identified the rules and justifications for presenting Ibn Malik's uncommon grammatical and morphological rules, and examined them analytically or morphologically in order to arrive at the results.This study was divided into two chapters, preceded by an introduction and prelude, and concluded with a summary of the study's conclusions.Chapter 1 covered the theoretical side. It provided a linguistic and idiomatic definition of "uncommon" and explained Ibn Malik's approach to presenting the uncommon rules. It also examined past research.Chapter 2 represented the practical and applied side of the study and included grammatical and morphological rules that began with the words "Nadar" (were uncommon), "Nader" (uncommon), and "Yandor" (are uncommon).
Keywords: Odd Grammatical Rules; Ibn Malik